Academic Pediatric Surgery Capacity Building in Vietnam Through PASS, a Pediatric Acute Surgical Support Course - Nguyen, Bich-Uyen; Holterman, Aixuan; Holterman, Mark; Dinh, Le-Thanh (Frontiers in Surgery, 2022)
Neonatal and pediatric surgical emergencies in Low and Low Middle Income countries remain a significant challenge in combatting the burden and inequities of global health. IPSAC-Vietnam is a small Non-Governmental Organization that has been engaged in a 12-year multi-pronged partnership with several children’s hospitals in Vietnam VN to enhance pediatric surgery capacity. We describe the health care, medical training and emergency system in VN as the background for IPSAC activities and development of Pediatric Acute Surgical Support (PASS) course. The course goal is to prepare health care personnel in the immediate management of neonatal/pediatric life-threatening surgical conditions and road injuries at their first point of entry into Vietnam hospitals. PASS is a horizontal outreach initiative that adopts an interprofessional, multidisciplinary, team-training, train-the-trainers, and outcome-based training approach. PASS can be used as a tool for sustainable horizontal capacity-building by champion leaders at the teaching children’s hospitals and medical universities in developing countries, to strengthen training for pediatric surgical emergencies, to integrate pediatric and pediatric surgical care and to advocate for a comprehensive approach to emergency care of the critically ill child.